Economic freedom in the context of the interference of the state in processes of the concentration of entrepreneurs - Rafał Stankiewicz (Ekonomia i Prawo, 2009)
Regulation, the purpose of which is to protect and develop the competitiveness of business activity carried out by business entities, is one of the most important elements of the legal order that guards the appropriate development of market economy. At present, it is based on the Act on protection of competition and consumers of February 16th, 2007. The assumption, according to which it is possible, in certain cases, to limit the constitutionally guaranteed economic liberty of some business entities, is an essential premise of such legal construction.        Economic liberty has not an absolute character. The scope of economic liberty depends, to a large extent, on the shape of the antimonopoly legislation in force in a given State. Interference of the antimonopoly regulation in the activity of entrepreneurs shall be restricted within the confines of the principle of proportionality. This restriction, as it seems, may concern such an extent of economic liberty of an entity or entities as will be indispensable for the realisation of the same subjective rights of its other beneficiaries. The principle of proportionality should  not bind only the legislative bodies, but also the bodies applying the law, in case the decision-making process during its realisation is simplified. The bodies applying the law should rely on the adequacy of applied instruments to the tasks and objectives assumed by the content of normative regulations.